DIGITAL LIBRARIES IN INDONESIA WITH SPECIAL EMPHASIS TO ACADEMIC LIBRARIES - Sulistiyo Basuki (BACA: Jurnal Dokumentasi dan Informasi, 2025)
There are many definitions about digital library, however, this paper used the definition taken from Digital Library Federation which stated that digital library as organizations that provide the resources, including the specialized staff, to select, structure, offer intellectual access to interpret, distribute, preserve the integrity of, and ensure the persistence over time of collections of digital works so that they are readily and economically available for use by defined community or set of communities (http://www.clir.org/diglib/about/strategic/htm). The elements that have been identified as common to those definitions are: I. A digital library is a managed collection of digital objects 2. The digital objects are created or collected according to principles of collection development. 3. The digital objects are made available in a cohesive manner, supported by services necessary to allow users to retrieve and exploit the resources just as they would any other library materials. 4. The digital objects are treated as long-term stable resources and appropriate processes are applied to them to ensure their quality and survivability (Deegan and Tanner 2002).